'Other patients become a secondary priority:' perceptions of Estonian frontline healthcare professionals on the influence of COVID-19 on health (in)equality and ethical decision-making. (2nd January 2022) - Lubi, Kadi; Simm, Kadri; Lempu, Kaja; Zameska, Jay; Eensalu-Lind, Angela
ABSTRACT: Background: The COVID-19 pandemic has posed many challenges to societies, individual healthcare systems and global public health. Manifestations of increasing health inequalities, social stigmatization and challenging ethical decision-making have been previously noticed. The aim of this article is to analyse the perceptions of frontline healthcare professionals regarding the potential impact of COVID-19 on the provision of healthcare services and the ethical challenges it may entail. Method: This research is a part of a larger research project which was conducted among frontline healthcare professionals in Estonia and used both quantitative and qualitative methods of data collection. In this article, answers to specific open-ended questions from the questionnaire ( n  = 116) and in-depth interviews ( n  = 8) were analysed. For data analysis, inductive content analysis was used. The research was granted ethical approval. Results: Findings show that through changes in regular and routinized practices in the provision of emergency medicine services, COVID-19 influences an increase of health inequality and social stigmatization. Other factors as well, such as lack of information about the disease, lack of resources, and fear of the disease, might reinforce these social phenomena. Additionally, from patient-centred and legal perspectives, issues of personal data management and privacy are highlighted. Conclusions: In addition to medical issues arising from COVID-19, countries worldwide should pay attention to the social and legal side effects of the illness to minimize health inequality and social stigmatization, as well as to moral, ethical and legal shortcomings in responses to the pandemic.